Analisis Tantangan Guru Dalam Menerapkan Pembelajaran Matematika Yang Inovatif di SDN Tundung Kecamatan Batukliang Tahun Ajaran 2020/2021 - Afriani, Sely; Affandi, Lalu Hamdian; Rosyidah, Awal Nur Kholifatur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
The aims of this research is to know challenges that faced by teachers in applying innovative math learning. This research use descriptive approach and qualitative method. The data were collected using interview and documentation. The data that has been collected were analyzed by using some steps; data reduction, data display, and conclusion drawing. The subject of this research is all teachers at SDN Tundung. Based on the analysis result, it was found that challenges that the teachers faced are covid-19 pandemic, online learning, decreased student interest in learning mathematics, and teachers who are not ready for innovative learning. Skills that needed to solve the problem are take advantage of existing media, increase the ability in using technology, complete the facilities and infrastructure, exchange information with professional friends about innovative learning.